The path of transboundary marine plastic waste management in China, Japan, and South Korea from the perspective of the blue economy - Hao, Huijuan; Jiang, Chenfan (Frontiers in Marine Science, 2023)
Marine plastic waste is one of the most difficult global ocean governance issues at present, and is also the focus of marine waste governance in the Yellow Sea and East China Sea region surrounded by China, Japan, and Republic of Korea (ROK). However, for lack of a binding marine environmental governance mechanism in the region, marine plastic waste management is quite fragmented. Although China, Japan, and South Korea are aware of the importance of this issue to their surrounding waters and development, inconsistent standards and progress in plastic-related policies, lack of support for the rules-based plastic waste governance, and the dilemma in cooperation due to political reasons have led to ineffective marine plastic waste management in the region, which threatens greatly the survival of marine life, human health and tourism on the coast. Therefore, the need for integration is increasing. The introduction of the blue economy inspires new ideas in marine plastic waste governance. Based on the market framework of marine plastic waste governance, opportunities for cooperation and complementarities of industrial value chains in green, low-carbon, recycling and technology industries between China, Japan and South Korea are becoming increasingly evident. Therefore, China, Japan and South Korea need to seize opportunities, come out of political dilemmas, and promote the conclusion of the regional marine waste governance agreement in order to develop China-Japan-ROK blue partnership.